2010
DOI: 10.2353/ajpath.2010.091010
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor δ Regulates Inflammation via NF-κB Signaling in Polymicrobial Sepsis

Abstract: The nuclear peroxisome proliferator-activated receptor δ (PPARδ) is an important regulator of lipid metabolism. In contrast to its known effects on energy homeostasis, its biological role on inflammation is not well understood. We investigated the role of PPARδ in the modulation of the nuclear factor-κB (NF-κB)-driven inflammatory response to polymicrobial sepsis in vivo and in macrophages in vitro. We demonstrated that administration of GW0742, a specific PPARδ ligand, provided beneficial effects to rats subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 42 publications
5
62
1
Order By: Relevance
“…We found three PPAR-related transcription factors along with THRA1 and the apoptosis-inducing gene FOXO3 correlated with many of these significantly increased b-oxidation and peroxidation metabolites. Although untested here, we hypothesize PPAR agonists improve survival in septic mice (43)(44)(45)(46) because of mitochondrial biogenesis leading to increased transcription of b-oxidation and BCAAdegradation associated genes. However, it should be noted that PPAR antiinflammatory effects have also been attributed to improved survival, and therefore links to mitochondrial function remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…We found three PPAR-related transcription factors along with THRA1 and the apoptosis-inducing gene FOXO3 correlated with many of these significantly increased b-oxidation and peroxidation metabolites. Although untested here, we hypothesize PPAR agonists improve survival in septic mice (43)(44)(45)(46) because of mitochondrial biogenesis leading to increased transcription of b-oxidation and BCAAdegradation associated genes. However, it should be noted that PPAR antiinflammatory effects have also been attributed to improved survival, and therefore links to mitochondrial function remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, in vivo studies by Lee et al showed that bone marrowed derived macrophages from Ppard deficient mice had reduced expression of pro-inflammatory factors such as Mcp-1 and Il-1β [22]. Conversely, the mouse macrophage cell line (RAW 264.7) stably overexpressing Ppard expressed higher levels of Mcp-1 and Il-1β than control cells suggesting that Ppard has pro-inflammatory effects although treatment with PPARD agonists have anti-inflammatory effects [22,33,34]. The underlying mechanism for these observations is that Ppard forms a complex with the inflammatory suppressor protein B cell lymphoma-6 (Bcl-6).…”
Section: Macrophagesmentioning
confidence: 92%
“…In the presence of ligand, Ppard releases Bcl-6, which is then free to exert its anti-inflammatory effects [22]. In addition, activation of Ppard induces the expression of genes that dampen chemokine receptor signaling and inflammatory mediators such as Tnfα [34,35]. Thus, Ppard appears to control the inflammatory status of the macrophage (Table 1) [22].…”
Section: Macrophagesmentioning
confidence: 97%
See 2 more Smart Citations